Governing uranium in India - Rajiv Nayan (Danish Institute for International Studies (DIIS), 2015)
India currently has 21 nuclear power reactors in operation, generating around three percent of the country's total electricity. To meet the increasing demands of a rising economy, India is expanding its nuclear energy grid from today's 5780 MW of energy to generate 20,000MWe by 2020. While the 2020 target will be delayed, the seven reactors currently under construction along with plans for 25 more will more than double India's demand for natural uranium in the coming decades. At the same time, India's uranium reserves are limited and low-grade, challenging its ability not only to continually feed future reactors, but also currently operating ones. As India has expanded domestic exploration efforts, it has also reached out to uranium suppliers abroad since a 2008 waiver by the Nuclear Suppliers Group (NSG) granted it access to foreign civilian and nuclear technology. India is thus a unique study as it becomes the only state outside of the Nuclear Non-proliferation Treaty (NPT) to engage in global nuclear commerce. This country report analyses the Indian nuclear industry's demand for natural uranium, its sources of supply and the legal framework that regulates the use of nuclear materials. It is part of the global Governing Uranium project, led by DIIS, which seeks to identify governance gaps in uranium accountability and control and to provide policy recommendations for improving front-end transparency, security and regulation.
Keywords: 300; Defense and security policy; India